Peran Kampus Dalam Pengembangan Karir Dan Kewirausahaan - Jayaun, Jayaun (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study explores the role of universities in career development and entrepreneurship. It aims to examine how universities contribute to shaping students' career paths and fostering entrepreneurial initiatives. The research focuses on identifying the various initiatives and programs implemented by universities to support career development and entrepreneurship among students. Methodologically, the study employs qualitative interviews and surveys to gather insights from students, faculty members, and industry professionals. Empirical findings highlight the significant impact of university-led initiatives in enhancing students' employability skills and entrepreneurial competencies. These initiatives include career counseling services, internships, entrepreneurship courses, startup incubators, and networking events. The study underscores the importance of universities in bridging the gap between academia and industry, thereby preparing students for the dynamic demands of the job market and equipping them with the necessary skills to succeed as entrepreneurs